Alkaline mineral addition to anoxic to hypoxic Baltic Sea sediments as a potentially efficient CO2-removal technique - Fuhr, Michael; Wallmann, Klaus; Dale, Andrew W.; Kalapurakkal, Habeeb Thanveer; Schmidt, Mark; Sommer, Stefan; Deusner, Christian; Spiegel, Timo; Kowalski, Jannes; Geilert, Sonja (Frontiers in Climate, 2024)
Recent studies have begun to explore the potential of enhanced benthic weathering (EBW) in the Baltic Sea as a measure for climate change mitigation. To augment the understanding of EBW under seasonally changing conditions, this study aims to investigate weathering processes under anoxia to hypoxia in corrosive bottom waters, which reflect late summer conditions in the Baltic Sea. Dunite and calcite were added to sediment cores retrieved from Eckernförde Bay (Western Baltic Sea) with a constant flow-through of deoxygenated, CO2-enriched Baltic Sea bottom water. The addition of both materials increased benthic alkalinity release by 2.94 μmol cm−2 d−1 (calcite) and 1.12 μmol cm−2 d−1 (dunite), compared to the unamended control experiment. These excess fluxes are significantly higher than those obtained under winter conditions. The comparison with bottom water oxygen concentrations emphasizes that highest fluxes of alkalinity were associated with anoxic phases of the experiment. An increase in Ca and Si fluxes showed that the enhanced alkalinity fluxes could be attributed to calcite and dunite weathering. First order rate constants calculated based on these data were close to rates published in previous studies conducted under different conditions. This highlights the suitability of these proxies for mineral dissolution and justifies the use of these rate constants in modeling studies investigating EBW in the Baltic Sea and areas with similar chemical conditions. Generally stable pH profiles over the course of the experiment, together with the fact that the added minerals remained on the sediment surface, suggest that corrosive bottom waters were the main driving factor for the dissolution of the added minerals. These factors have important implications for the choice of mineral and timing for EBW as a possible marine carbon dioxide removal method in seasonally hypoxic to anoxic regions of the Baltic Sea.